Kenya : Technical Assistance Report-Further Review of Rebased GDP Estimates. (IMF Staff Country Reports; Country Report, 2022)
A Technical Assistance (TA) mission was conducted in July 2021 to review the data sources and methods used to produce revised estimates of the Kenyan National Accounts (NA) for the period 2009-2019. The mission also provided guidance on producing a revision report to be published at the time of the release.